ASM551: Networking and telecommunication systems / Faculty of Business Management - UiTM, Faculty of Business Management (2019)
This course describes the role of telecommunications and networking in business offices and organizations. It deals with the components and procedures in the applications of telecommunications and networking. In addition, the course also examines a wide range of new and emerging telecommunications technologies and networking and use of modern telecommunications and networking for strategic advantage.